Public perception of the Ombudsman - Anna Solomon (Pacific Journalism Review, 1997)
The Ombudsman Commission's ability in getting results again reinforces the public's confidence in the Ombudsman office and what it stands for - standing up for the rights of individuals who would otherwise be ignored by the powers that be.